2018
DOI: 10.3389/fmicb.2018.02181
|View full text |Cite
|
Sign up to set email alerts
|

Common Cervicovaginal Microbial Supernatants Alter Cervical Epithelial Function: Mechanisms by Which Lactobacillus crispatus Contributes to Cervical Health

Abstract: Cervicovaginal (CV) microbiota is associated with vaginal health and disease in non-pregnant women. Recent studies in pregnant women suggest that specific CV microbes are associated with preterm birth (PTB). While the associations between CV microbiota and adverse outcomes have been demonstrated, the mechanisms regulating the associations remain unclear. As the CV space contains an epithelial barrier, we postulate that CV microbiota can alter the epithelial barrier function. We investigated the biological, mol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
84
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(97 citation statements)
references
References 163 publications
8
84
0
Order By: Relevance
“…Previous work using HeLa cells showed that a vaginal strain of L. crispatus can induce NF-ķB activation and yet maintain low levels of several proinflammatory cytokines [63]. Another report, using human ectocervical and endocervical cell lines treated with soluble products produced by L. crispatus induced responses that may result in cervical epithelial barrier protection, including secretion of IL-10 -the same response we found in our experiments with trophoblasts, and that can be interpreted as being conducive to immunomodulation [64]. Recent evidence in non-pregnant women suggests that the endometrial cavity may have a characteristic microbiota with low biomass [65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Resultssupporting
confidence: 83%
“…Previous work using HeLa cells showed that a vaginal strain of L. crispatus can induce NF-ķB activation and yet maintain low levels of several proinflammatory cytokines [63]. Another report, using human ectocervical and endocervical cell lines treated with soluble products produced by L. crispatus induced responses that may result in cervical epithelial barrier protection, including secretion of IL-10 -the same response we found in our experiments with trophoblasts, and that can be interpreted as being conducive to immunomodulation [64]. Recent evidence in non-pregnant women suggests that the endometrial cavity may have a characteristic microbiota with low biomass [65][66][67][68][69][70][71][72][73][74][75][76][77].…”
Section: Resultssupporting
confidence: 83%
“…Our study did not reveal the molecules involved in the physical disruption of the hEC barrier by these vaginal microorganisms, but the data possibly indicate that enhancement of phosphatase activity is among the major underlying mechanisms that lead to TJ dysregulation of the host cervicovaginal epithelium. Disruption of this barrier has been attributed to G. vaginalis (10,17,32), but the mechanisms are not yet understood and no phosphatases have been claimed to be involved. On the other hand, phosphatase activity has been found in various cellular compartments of T. vaginalis, including on its surface and in secreted fractions (50); those findings have been recently supported by proteomics data (51,52).…”
Section: Discussionmentioning
confidence: 99%
“…A link between these events and the composition of the vaginal microbiota has been claimed, and the CST-IV bacterium G. vaginalis, in particular, has been associated with this process (10,15,17,31). Protective lactobacilli, on the other hand, are known to promote cervical health by mitigating effects of proinflammatory molecules and counteracting G. vaginalisinduced disruption of the cervicovaginal barrier (32).…”
mentioning
confidence: 99%
“…Sierra et al evaluated the expression of certain miRNAs after contact to bacteria-free supernatants of Gardnella vaginalis (G. vaginalis), Lactobacillus crispatus (L. crispatus), and Lactobacillus iners (L. iners). Remarkably, the upregulation of miRNA-15a, miRNA-143, miRNA-145, miR-146, miR-223, and miR-148 by G. vaginalis bacteria-free supernatants and miR-146, miRNA-193b, and miR-223 by L. iners bacteria-free supernatants with no modification by L. crispatus reveals the existence of a bacterial species-specific modification in miRNA expression profiles [27].…”
Section: Microbiota and Ovarian Cancermentioning
confidence: 92%